Legal Politics in Combating Corruption During Indonesia's Era of Regional Autonomy - Simamora, Janpatar; Manik, Risma Elfrida Esther (Universitas Negeri Semarang, 2025)
Efforts to eradicate corruption have not been fully effective, especially after the implementation of regional autonomy, where corruption cases have increased significantly. This paper examines the key factors driving corruption in decentralized governance, particularly in Indonesia, and evaluates the effectiveness of legal policies implemented by the government. Using a normative juridical research approach with a descriptive-analytical method, this study identifies three major contributors to corruption under regional autonomy: excessive authority without adequate oversight, high political costs, and self-serving governance among regional officials. Despite the establishment of various anti-corruption regulations, the enforcement mechanisms remain inconsistent and ineffective. The paper argues that the success of anti-corruption policies requires not only legal reforms but also institutional commitment, ethical governance, and structural enforcement mechanisms. Legal politics should be directed toward strengthening monitoring systems, improving governance capacity, and ensuring strict legal enforcement to create a deterrent effect.